2011
DOI: 10.1007/s11262-011-0619-3
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Iranian Potato virus S isolates

Abstract: Two hundred forty potato samples with one or more symptoms of leaf mosaic, distortion, mottling and yellowing were collected between 2005 and 2008 from seven Iranian provinces. Forty-four of these samples tested positive with double-antibody sandwich enzyme-linked immunosorbent assays (DAS-ELISA) using a Potato virus S (PVS) polyclonal antibody. Of these 12 isolates of PVS were selected based on the geographical location for biological and molecular characterization. The full coat protein (CP) and 11K genes fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
7
0
3

Year Published

2012
2012
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 22 publications
1
7
0
3
Order By: Relevance
“…Different isolates of potato virus S (PVS), which is closely related to PVM, have been classified into two biologically different strains. Interestingly, it was found that this differentiation is reproducible by phylogenetic analysis of the PVS CP gene (Cox and Jones, 2010;Xu et al, 2010;Salari et al, 2011;Tabasinejad et al, 2014). This finding confirmed that the CP region is a suitable genomic region to study the genetic diversity of carlaviruses.…”
Section: Introductionsupporting
confidence: 55%
“…Different isolates of potato virus S (PVS), which is closely related to PVM, have been classified into two biologically different strains. Interestingly, it was found that this differentiation is reproducible by phylogenetic analysis of the PVS CP gene (Cox and Jones, 2010;Xu et al, 2010;Salari et al, 2011;Tabasinejad et al, 2014). This finding confirmed that the CP region is a suitable genomic region to study the genetic diversity of carlaviruses.…”
Section: Introductionsupporting
confidence: 55%
“…Based on this threshold, isolates within the GFLV-G clade were divided into 31 genotypes and those of GFLV-Ir were divided into 6 genotypes. Such scoring approaches have been previously used for genotyping of mastreviruses (Muhire et al, 2013), potato virus S (Salari et al, 2011) and potato virus M (Tabasinejad et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Trabajos similares al aquí presentado, que evalúan los niveles de diversidad de PVS con base en secuencias de CP, han encontrado una base genética más estrecha para los aislamientos de PVS caracterizados en diferentes regiones. Así por ejemplo, Salari et al (2011) al evaluar los niveles de diversidad de 12 aislamientos de PVS procedentes de Irán, encontraron que todos los aislamientos correspondían a la raza PVS O y que su diversidad global oscilaba entre 92.5 y 99.1%; mientras que Lambert et al (2012) evaluando la variabilidad genética de aislamientos de PVS obtenidos en cultivos de papa de Tasmania (Australia), encontraron que éstos compartían niveles de identidad superiores al 95%, independientemente de causar infecciones sistémicas (PVS O-CS ) o locales (PVS O ) sobre C. quinoa. Similarmente, Lin et al (2009) evaluaron las secuencias completas de dos aislamientos de PVS de EEUU, y encontraron que éstos compartían una identidad global para todo el genoma de 98% y de 98.6% para el gen de CP.…”
Section: Discussionunclassified
“…Los genes 2, 3 y 4 comprenden el triple bloque de genes (TGB), que participan en el movimiento intra e intercelular del virus, mientras que el gen 5 de ~970nt, codifica para la cápside viral (CP) de 34kDa. Este gen se traslapa con el gen 6 que codifica para una proteína rica en cisteína de unión a ácidos nucleicos (NABP), involucrada en la transmisión por áfidos, silenciamiento de genes del hospedante y en la replicación viral (Matoušek et al 2005, Lin et al 2009, Salari et al 2011.…”
unclassified
See 1 more Smart Citation